The Performance of a Fixed-Bed Anaerobic Bioreactor Using Sulfate-Reducing Bacterial Consortium from Sikidang Crater Sediments - Andriyanto Andriyanto; Wahyu Wilopo; Endah Retnaningrum (Indonesian Journal of Chemistry, 2020)
This research explored the performance of a fixed-bed anaerobic bioreactor system (FBR) using sulfate-reducing bacteria (SRB) from the sediment of Sikidang Crater in Indonesia. Indonesian natural zeolite was used as an inert medium in this bioreactor system. This bioreactor performance was analyzed based on its sulfate reduction efficiency, Cu removal, pH profile, SRB growth, and the changes in mineral composition of the zeolite surface. Based on a batch experiment, the FBR system was operated at 30 °C with a hydraulic retention time (HRT) of 7 days using a zeolite dose of 100 g/L. After its operation, a large amount of SRB (up to 1.5 × 105 cells/mm2) was entrapped and present in the zeolite. This bacterial consortium could reduce sulfate and copper by around 68% and 99.96%, respectively. In addition, the pH value of the bioreactor changed to neutral, which indicated a good performance of the operation. The result of the Energy-Dispersive X-ray (EDX) confirmed that copper removal was caused by the formation of copper-sulfide precipitation. Mapping also revealed that both copper and sulfur were precipitated at the same location.